The Madrasah schools in Marawi City their educational objectives, practices and institutional societal roles - Nunag, Dominador E. 1918- (1970)
The study identifies the educational objectives, practices, and institutional roles of the Madrasah schools in Marawi City to the Maranao society in particular, and to the Philippine society in general. Results of the study aim to help school officials, policy-makers, community and religious leaders, laymen, and others get involved in community development, especially in the formulation of sound educational policies and to develop a bridge to national solidarity - unity in diversity.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Islam -- Education